Genesis : procreation and the politics of identity - Brett, Mark G. (London ; New York : Routledge, 2000)
Mark Brett places the first book of the Bible firmly within its sociopolitical context. He argues that it can be read as resistance literature and that the editors of Genesis ŵere directly engaged with contemporary issues.
Includes bibliographical references (pages 155-162) and indexes.
Print version record.
Master record variable field(s) change: 630
Keywords: Bible. -- Socio-rhetorical criticism; Bible. -- Socio-rhetorical criticism; RELIGION -- Biblical Studies -- Old Testament; Electronic books